Application of the Lean Manufacturing methodology to increase production in the manufacturing company INDEMUG SAC (LACCEI, 2024)
This research work was carried out taking into account the need for improvement in the production processes of a manufacturing company. Therefore, the objective is to determine to what extent the application of the Lean Manufacturing methodology increases the production of the manufacturing company INDEMUG SAC in the year 2022. The study considered a population of 105 plates worked during 2021, taking them also as a convenience sample. In addition, validated instruments such as data registration forms, question scripts, a 5S compliance control form and company documentation were used. The main results were an increase of 46 plates worked by 2022, an increase in labour output of 0.019 plates worked/h-h-h and a 19% increase in order fulfilment. Finally, an economic evaluation was carried out where an NPV of S/15,213.33 (3956.47 dollars), IRR of 1.72 and a B/C of 3.69 were obtained. Therefore, the application of this methodology was profitable for the company.